2010
DOI: 10.1074/jbc.m109.064311
|View full text |Cite
|
Sign up to set email alerts
|

Large T Antigen Promotes JC Virus Replication in G2-arrested Cells by Inducing ATM- and ATR-mediated G2 Checkpoint Signaling

Abstract: The human polyomavirus JC virus (JCV) 2 is the causative agent of progressive multifocal leukoencephalopathy (PML), a fatal demyelinating disease of the central nervous system. JCV infection usually occurs during childhood, but remains subclinical. However, opportunistic reactivation of JCV results in the development of PML in individuals with a compromised immune system, such as those with acquired immunodeficiency syndrome (AIDS) or advanced-stage malignant tumors, or those recently having undergone organ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
79
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 51 publications
11
79
1
Order By: Relevance
“…Similar to the original findings for SV40, LTag binding to the retinoblastoma pRB family proteins modulates the activity and abundance of host cell transcription factors (47). LTag also counteracts the p53-mediated apoptosis which would be caused by accumulating DNA fragments and metabolic exhaustion, as reviewed elsewhere (48), and shifts the cell into a proliferative G2/S state by activating ATM-and ATR-mediated pathways (49). The sTag is a cytoplasmic protein of 172 aa.…”
Section: Steps Of the Jcpyv Life Cyclementioning
confidence: 57%
“…Similar to the original findings for SV40, LTag binding to the retinoblastoma pRB family proteins modulates the activity and abundance of host cell transcription factors (47). LTag also counteracts the p53-mediated apoptosis which would be caused by accumulating DNA fragments and metabolic exhaustion, as reviewed elsewhere (48), and shifts the cell into a proliferative G2/S state by activating ATM-and ATR-mediated pathways (49). The sTag is a cytoplasmic protein of 172 aa.…”
Section: Steps Of the Jcpyv Life Cyclementioning
confidence: 57%
“…Studies of other polyomaviruses implicate the DDR machinery in replication and monomeric resolution of viral genomes, as well as repair of cellular DNA damage caused by the viruses (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…Polyoma viral replication requires S-phase progression on the part of infected host cells. In particular, previous studies had revealed that JCV genome replication may be facilitated by virally induced cell cycle arrest in G2, prior to the G2/M transition (23). In light of the apparent delay in viral replication in human oligodendroglia, relative to astrocytes and GPCs, we next asked whether infected astrocytes and oligodendrocytes differ in their efficiency of S/G2 traversal.…”
Section: Jcv Efficiently Infects Astroglia and Their Progenitors In Cmentioning
confidence: 98%
“…Because p53 is phosphorylated at Ser15 when DNA damage is detected, phospho-p53(Ser15) expression may be used as a marker of DNA damage, as well as its associated cell cycle arrest at G2/M (23)(24)(25). We found that a significantly higher proportion of T-Ag + astrocytes coexpressed phospho-p53(Ser15) than did uninfected T-Ag -cells ( + glia in the corpus callosum of a human glial chimeric Rag2 -/-Mbp shi/shi mouse 12 weeks after type 1A (Mad-1) JCV infection showed the predominant white matter spread of virus in these mice, which manifested both oligodendrocytic and astrocytic infection (compare with the Rag1 -/-section in C).…”
Section: Jcv Efficiently Infects Astroglia and Their Progenitors In Cmentioning
confidence: 99%